Impact of immediate initiation of antiretroviral therapy on HIV patient satisfaction. (1st February 2020) - Ogbuoji, Osondu; Geldsetzer, Pascal; Wong, Cebele; Khan, Shaukat; Mafara, Emma; Lejeune, Charlotte; Walsh, Fiona; Okello, Velephi; Bärnighausen, Till
Abstract : Objectives: Immediate ART (or early access to ART for all, EAAA) is becoming a national policy in many countries in sub-Saharan Africa. It is plausible that the switch from delayed to immediate ART could either increase or decrease patient satisfaction with treatment. A decrease in patient satisfaction would likely have detrimental consequences for long-term retention and adherence, in addition to the value lost because of the worsening patient experience itself. We conducted a pragmatic stepped-wedge cluster-randomized controlled trial (SW-cRCT) to determine the causal impact of immediate treatment for HIV on patient satisfaction. Design: This seven-step SW-cRCT took place in 14 public-sector health facilities in Eswatini's Hhohho region, from September 2014 to August 2017. Methods: During each step of the trial, we randomly selected days for data collection at each study facility. During these days, a random sample of HIV patients were selected for outcome assessment. In total, 2629 patients provided data on their overall patient satisfaction and satisfaction with the following four domains of the patient experience using a five-point Likert scale: wait time, consultation time, involvement in treatment decisions, and respectful treatment. Higher values on the Likert scale indicated lower patient satisfaction. We analyzed the data using a multilevel ordered logistic regression model with individuals at the first level and health facilities at the second (cluster) level. Results: The proportional odds ratio (OR) comparing EAAA to control was 0.91 (95% CI 0.66–1.25) for overall patient satisfaction. For the specific domains of the patient experience, the ORs describing the impact of EAAA on satisfaction were 1.04 (95% CI 0.61–1.78) for wait time, 0.90 (95% CI 0.62–1.31) for involvement in treatment decisions, 0.86 (95% CI 0.61–1.20) for consultation time, and 1.35 (95% CI 0.93–1.96) for respectful treatment. These results were robust across a wide range of sensitivity analyses. Over time – and independent of EAAA – we observed a worsening trend for both overall patient satisfaction and satisfaction in the four domains of the patient experience we measured. Conclusion: Our findings support the policy change from delayed to immediate ART in sub-Saharan Africa. Immediate (versus delayed) ART in public-sector health facilities in Eswatini had no effect on either overall patient satisfaction or satisfaction with four specific domains of the patient experience. At the same time, we observed a strong secular trend of decreasing patient satisfaction in both the intervention and the control arm of the trial. Further implementation research should identify approaches to ensure high patient satisfaction as ART programs grow and mature. Abstract : Supplemental Digital Content is available in the text